Low-Dose Steroid Therapy Is Associated with Decreased IL-12 Production in PBMCs of Severe Septic Patients - Chen, Tien-Hsing; Chuang, Duen-Yau; Shih, Chi-Chung; Wu, Huang-Pin (Mediators of Inflammation, 2016)
Background. Sepsis-induced immunosuppression may result in higher mortality rates in patients. Methods. We examined the relationship of cytokine responses from stimulated peripheral blood mononuclear cells (PBMCs) and monocyte human leukocyte antigen-DR (HLA-DR) expression (days 1 and 7) with low-dose steroid therapy in 29 septic patients. Patients were treated according to the guidelines. Thirty healthy controls were enrolled for validation. Results. Eighteen patients were prescribed low-dose steroids and 11 were not. Interleukin- (IL-) 12 responses in patients without low-dose steroid therapy on days 1 and 7 were higher than those with low-dose steroid therapy. Compared to day 1, IL-12 responses significantly increased on day 7 in patients without low-dose steroid therapy. After regression analysis, the change in the IL-12 response from day 7 to day 1 was found to be independently associated with the low-dose steroid therapy. There was no difference in monocyte HLA-DR expression between patients treated with and without low-dose steroid on day 1 or 7. No change in monocyte HLA-DR expression from day 7 to day 1 was observed in patients with or without low-dose steroid therapy. Conclusion. Decreased IL-12 response was associated with the low-dose steroid therapy in PBMCs of septic patients.